Capital united? Business unity in regulatory politics and the special place of finance. Issue 1 (1st September 2015) - Young, Kevin; Pagliari, Stefano
Abstract: While organized business is a key actor in regulatory politics, its influence is often conditional on the level of unity or conflict occurring within the business community at any given time. Most contemporary regulatory policy interventions put pressure on the normal mechanisms of business unity, as they are highly targeted and sector‐specific. This raises the question of how business unity operates across a highly variegated economic terrain in which costs are asymmetric and free‐riding incentives are high. In this paper, we empirically assess patterns of business unity within regulatory policymaking across different regulated sectors. Our analysis utilizes data from hundreds of regulatory policy proposals and business community reactions to them in the telecommunications, energy, agriculture, pharmaceutical, and financial sectors over a variety of institutional contexts. We find considerable empirical support for the "finance capital unity" hypothesis – the notion that the financial sector enjoys more business unity than other regulated sectors of the economy. When the financial sector is faced with new regulations, business groups from other sectors frequently come to its aid.